HYGIENIC ASSESSMENT OF NUTRITIONAL STATUS IN PATIENTS WITH TUMOR DISEASE - Ortiqov B.B., Omonova G.F., Omonov J.P. (Prospects for innovative technologies in science and education, 2026)
The composition of the diet changes significantly depending on the seasons of the year. Seasonal dietary habits lead to an imbalance in the ratio of macronutrients (proteins, fats, and carbohydrates), which directly affects metabolic processes, immune response, and inflammatory processes [1,6,8]. This is especially important in patients with chronic diseases, including those with tumor diseases of the digestive system, where an unbalanced diet may contribute to the intensification of inflammatory processes, worsening of clinical symptoms, and deterioration of the disease course